Pearls and Irritations - Menadue, J. L. (John Laurence), 1935- (Australia : John Menadue, 2013)
Blog of 'John Menadue', a businessman and a public commentator, and formerly a senior public servant and diplomat.
Title from title screen (viewed on 20 August 2013)
Mode of access: Available online. Address as at 25/2/14
Selected for archiving
Keywords: Health -- Australia -- Blogs; Human rights -- Australia -- Blogs; Illegal aliens -- Australia -- Blogs; Australia -- Officials and employees -- Blogs; Australia -- Politics and government -- Blogs; Australian